Psychological distress and COVID-19 infection in students at the Franklin Roosevelt Private University of Huancayo, 2022. - Zavala Figueroa , Nataly Johanna (2023)
Objective: To determine the levels of psychological distress according to the severity of the COVID-19 infection in the students of the Universidad Privada de Huancayo Franklin Roosevelt, 2022. Material and methods: Basic study of comparative design. For comparisons between the severity of COVID-19 infection and the presence of psychological distress, the Kruskal Wallis H test was used. Results: Regarding the age of the students, 56.5% are in the range of 18 to 25 years, 32.1% from 26 to 35 years, 9.8% from 36 to 45 years and only 1.5% are older. 45 years old, depending on gender, female 75.9% and male 24.1%. Severity due to COVID-19 showed a mild level with 60.3%, moderate with 39.1% and only 0.5% as severe. In the level of psychological distress, 15.3% presented the low level, moderate 33%, high 29.4% and very high 22.3%. Conclusions: It was determined that there are differences in the level of psychological distress between the students who presented mild, moderate and severe severity of the COVID-19 infection (X2=17.7, p < 0.05). Likewise, regarding the sex and age of the students, the levels of psychological distress presented significant differences for each of the values ​​of the variables under study; (X2= 20.575; p=0) and (X2=13.047) respectively.